Obtaining of Nanoapatite in Ti-7.5Mo Surface After Nanotube Growth - Escada, A. L. A. [UNESP]; Machado, J. P. B.; Nakazato, Roberto Zenhei [UNESP]; Alves Claro, A. P. R. [UNESP] (Trans Tech Publications Ltd, 2012)
Titanium and their alloys have been used for biomedical applications due their excellent mechanical properties, corrosion resistance and biocompatibility. However, they are considered bioinerts materials because when they are inserted into the human body they are cannot form a chemical bond with bone. In several studies, the authors have attempted to modify their characteristic with treatments that changes the material surface. The purpose of this work was to evaluate obtaining of nanoapatite after growing of the nanotubes in surface of Ti-7.5Mo alloy. Alloy was obtained from c.p. titanium and molibdenium by using an arc-melting furnace. Ingots were submitted to heat treatment and they were cold worked by swaging. Nanotubes were processed using anodic oxidation of alloy in electrolyte solution. Surfaces were investigated using scanning electron microscope (SEM), FEG-SEM and thin-film x-ray diffraction. The results indicate that nanoapatite coating could form on surface of Ti-7.5Mo experimental alloy after nanotubes growth.
Keywords: Titanium alloys; Calcium Phosphate; Nanotubes TiO2